Migrant women’s perception toward cervical and breast cancer screening in Türkiye: a qualitative analysis - Zeynep Meva Altaş; Mehmet Akif Sezerol (BMC Public Health, 2025)
Abstract Introduction This study aims to investigate the knowledge, attitudes, and behaviors of Syrian migrant women regarding breast and cervical cancer screenings in the Sultanbeyli district of Istanbul. Methods The women were recruited from Extended Migrant Health Centre, which is a primary health care institution in Istanbul. In August 2024, face-to-face interviews were conducted using an open-ended, semi-structured question form administered by a nurse experienced in qualitative research. Sociodemographic information, their thoughts on cancer, information on the types of cancers screened and sources of information, their participation in cancer screenings, and their perspectives on cancer screenings were asked. Results In depth interviews were conducted with 40 migrant women. Four main themes and thirteen sub-themes were identified. These themes include “Opinions about the cancers and information about the cancer screenings” “Attitudes about the cancer screening program” “Perspectives on preventive measures against cancers” and “Problems in access to health services”. Women mostly described cancer as a serious, incurable, and fatal disease. Despite this perception, almost half of the participants had not attended cancer screening programs. The majority said they did not undergo screening because they had no symptoms. The other main barriers for participation included lack of knowledge, fear of receiving a negative result, or fear of the procedures involved. Conclusions Based on this study, migrant women have low level of attendance to breast and cervical cancer screening programs. Besides, they lack adequate information about breast cancer and cervical cancer, the screening protocols and preventive measuremets.